2019
DOI: 10.1016/j.memsci.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Continuous juice concentration by integrating forward osmosis with membrane distillation using potassium sorbate preservative as a draw solute

Abstract: A green and sustainable technique is desired for juice concentration to increase its shelf life and save the transportation cost. In this study, we investigated an integrated forward osmosis-membrane distillation (FO-MD) process for juice concentration and developed a food preservative potassium sorbate as a renewable draw solute. The upstream FO process was used to concentrate apple juice in ambient operation conditions for preserving juice nutrition and flavor. Potassium sorbate preservative was developed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 41 publications
1
37
1
Order By: Relevance
“…An et al used potassium sorbate (a common preservative in the food industry) as a draw solution thanks to its high osmotic potential and low reverse permeation flux. In their study, apple juice concentrate flavours were not altered and potassium sorbate in the juice concentrate was in line with legislation [ 51 ]. Another limitation is the membrane fouling and enhanced concentration polarisation that may occur especially with complex liquids and in the presence of proteins (pectins, etc.)…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 93%
“…An et al used potassium sorbate (a common preservative in the food industry) as a draw solution thanks to its high osmotic potential and low reverse permeation flux. In their study, apple juice concentrate flavours were not altered and potassium sorbate in the juice concentrate was in line with legislation [ 51 ]. Another limitation is the membrane fouling and enhanced concentration polarisation that may occur especially with complex liquids and in the presence of proteins (pectins, etc.)…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 93%
“…The typical technologies employed for fruit juices concentration are multi-stage vacuum evaporation, freezing technique, and membrane (NF & RO) processes. These processes possess some drawbacks, such as being energy-intensive, have negative impacts on juice quality, and high membrane fouling issues [74]. Currently, FO has been proposed as an alternative technology for fruit juice concentration, aligns with its working principles [75].…”
Section: Bioproducts and Food Industrymentioning
confidence: 99%
“…Though numerous studies have demonstrated the capability of FO in concentrating the fruit juices to a desirable concentration, studies on integrated FO process for this application have been rare. An integrated FO process reported in the literature was the integration of FO with MD where the latter process served to regenerate the draw solution and to ensure continuous operation of FO process [74]. The integrated FO-MD process managed to increase the total soluble solid of apple juice from 10.6°Brix to 45.1°Brix, which was twice the value achieved by an RO concentration process.…”
Section: Bioproducts and Food Industrymentioning
confidence: 99%
“…Forward osmosis (FO), the most common osmotically driven membrane process, stands out as the most promising alternative for RO processes due to its inherently low fouling tendency, easier fouling removal, and energy efficiency when compared to pressure-driven-type membrane processes [16][17][18][19]. Owing to these attractive inherent features, FO has been used as a concentration and dilution process in diverse areas including food processing [21][22][23][24], wastewater treatment [25][26][27], desalination [28][29][30][31], and power generation [3,32]. In medical application, FO assists in controlling the release of drugs with low solubility [33,34] and in preserving properties of feed (nutrition, taste, quality, etc.)…”
Section: Introductionmentioning
confidence: 99%